2022
DOI: 10.3390/ijerph19138164
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Daily Physical Activity and Locomotive Syndrome in Community-Dwelling Japanese Older Adults: A Cross-Sectional Study

Abstract: This study aimed to evaluate the association between locomotive syndrome (LS) and daily physical activity (PA) in community-dwelling older adults. This cross-sectional study included 80 healthy Japanese older adults (40 men and 40 women; age: 60–79 years). Habitual daily PA was evaluated using a triaxial wrist accelerometer. Participants were divided into two groups based on the results of the two-step test, stand-up test, and 25-question geriatric locomotive function scale. Binomial logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…However, in this study, 11.6% of the participants had LS and 12.8% had anemia. These prevalence rates are similar to those reported in several previous studies on community-dwelling older adults, with prevalence rates of 12% 27 and 14% 28 for LS, and 10% 29 and 15.2% 20 for anemia. Fourth, we did not obtain any data regarding factors associated with anemia, such as heart failure and chronic obstructive pulmonary disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in this study, 11.6% of the participants had LS and 12.8% had anemia. These prevalence rates are similar to those reported in several previous studies on community-dwelling older adults, with prevalence rates of 12% 27 and 14% 28 for LS, and 10% 29 and 15.2% 20 for anemia. Fourth, we did not obtain any data regarding factors associated with anemia, such as heart failure and chronic obstructive pulmonary disease.…”
Section: Discussionsupporting
confidence: 90%
“…25 Moreover, symptoms of anemia such as fatigue, weakness, and vertigo can reduce physical activity. 26 Decreased physical function and activity may be associated with decreased locomotive functions 27,28 and may increase the risk of LS. In future studies on LS and anemia, researchers should consider factors such as physical function and activity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that spending ≥28.01 minutes on moderate to vigorous PA (≥3.0 METs) was significantly associated with a lower risk of LS in older women (reference, ≤27.99 minutes; age-adjusted OR, 0.12), 14 whereas resting and sitting behaviors (<1.5 METs) were not related to LS. Our study examined the associations between PA during leisure and work separately, accounting for potential confounders, and identified specific PA-related factors associated with LS in young to middle-aged participants.…”
Section: Discussionmentioning
confidence: 92%
“… 13 Furthermore, moderate PA (≥3.0 metabolic equivalents [METs]) was associated with a decreased risk of LS in community-dwelling elderly women. 14 Therefore, evaluating PA, including sedentary behavior, is crucial for improving mobility function and health in middle-aged and elderly individuals. Office workers who sat during working hours also sat for longer periods outside work.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the GLFS-25 is widely recognized in Japan, Iran, Brazil, China, and other countries for LS screening across different societal age groups [ [18] , [19] , [20] ]. It is increasingly being used for LS screening among hospital orthopedic patients, individuals with rheumatoid arthritis, intensive care unit patients, and those experiencing debilitation [ [21] , [22] , [23] ]. In Japan, the GLFS-25 has been employed as a comprehensive tool for MF assessment, providing early warnings about MF issues [ 24 ].…”
Section: Introductionmentioning
confidence: 99%